CORPORATE SOCIAL RESPONSIBILITY AND PROFITABILITY IN THE PRIMARY CONSUMPTION SECTOR ON THE INDONESIA STOCK EXCHANGE (International Journal of Innovative Technologies in Economy, 2025)
In the Primary Consumption Sector, there is a need to concentrate on Corporate Social Responsibility (CSR) by analyzing the relationship between CSR and company performance, reflected in profitability ratios. This research adopts a quantitative approach and test Classical Assumption (normality, multicollinearity, and autocorrelation). The population in this company data consists of 123 companies. The analysis results indicate that CSR disclosure, partially, does not have a significant impact on profitability among 61 companies listed on the Indonesia Stock Exchange (IDX) in 2022. In other words hypothesis testing suggests that CSR disclosure does not have a significant effect on profitability ratios.